DESIGN INTERVENTION ON THE MOTIF PATTERNS OF “KAPDA GONDA” CRAFT OF DONGRIA KONDH TRIBE OF ORISSA - Rastogi, Twinkle (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India is a country with rich heritage of traditional textiles. It is a cluster of art and crafts of various communities and tribes. Tribal textiles are distinguished by their one-of-a-kindness, which reflects racial feelings and cultural identity. “Dongria Kondh” is a tribe from Odisha, lives on the hills of Niyamgiri, particularly on Rayagadha district. The importance of this community is that their arts and crafts reflect the importance of the mountains strain. The triangular design on the walls of the village and the colourful cloth embroidery they wear called "Kapda Gonda”. The design for adornment of kapda gonda reflects with the ethnic identity. The research process includes ethnographic investigation to profile social and cultural importance of Kapda Gonda in the form of interview of artisans for the process and embroidery involved in “Kapda Gonda”. The main purpose of the study is to provide training to the artisans to explore new ways of design intervention in the patterns of traditional motifs of Kapda Gonda to create awareness of their own craft flexibility within their community. With design intervention in Kapda Gonda motifs the artisans could make wide range of motifs for the modern society.